Magnetic barcodes in molecular medicine - Byrne, Fiona N. (Trinity College (Dublin, Ireland). School of Physics, 2010)
The need for faster and more sensitive diagnostic systems for the early detection of many life-threatening diseases is the driving force behind the work in this thesis. A lab-on-a-chip prototype device incorporating a sensor and a magnetic barcoded nanowire functionalised with biomolecules has the potential to revolutionise the current methods of disease diagnosis. The fabrication of metallic nanowires by electrodeposition into templates with nanometre diameters (~10 - 200 nm) in the late 1960s has paved the way for their endless applications. Electrochemical deposition enables the composition, dimensions and most importantly, the properties of thin films and nanowires to be easily controlled and modified. Many groups have studied the structural and magnetic properties of single component, alloy and multilayered or multisegmented films and nanowires produced by this method. However, the use of barcoded magnetic nanowires as potential nanocarriers of biomolecules had yet to be explored.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.